The Factors Affecting to Personnel Management of School Under Secondary Educational Service Area Office 42: The Factors Affecting to Personnel Management of School Under Secondary Educational Service Area Office 42 - Sukpuang, Likhit (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2021)
The objectives of this research were to study the level of factors affecting personnel management, to study the level of personnel management, to study the co-relation between factors affecting personnel management and personnel management and to create predictive equation of personnel management of school. The sample group used are director, deputy director, personnel supervisor and leader of all learning groups totaling 242 people using simple random sampling. The research tool used was a 5- point rating scale questionnaire, with a reliability coefficient of 0.93. The statistics used for data analysis were frequency, percentage, mean, standard deviation. Pearson correlation coefficient and Stepwise multiple regression analysis. The research findings were as follows: The level of factors that affect personnel management of school overall and each aspect were at a high level. The level of personnel management of school overall was at a high level. The co-relation between factors and management has positive relationship to personnel management of school has a positive relationship between 0.43 - 0.90 with statistical significance at the level of 01. And Factors affecting personnel management of the school are that technology, characteristics of administrators, budget and the policies and practices. Is a predictor that can predict together with a statistically significance at .05 level, Predict the management of school personnel by 89%.